A planar balanced‐to‐balanced filtering power divider with in‐band common‐mode suppressions and self‐isolation. Issue 7 (15th April 2022) - Wu, Gangxiong; Xu, Kai; Shi, Jin
Abstract: A compact balanced‐to‐balanced (BTB) filtering power divider (FPD) with in‐band common‐mode (CM) suppressions based in a single‐layer substrate‐integrated waveguide (SIW) is presented in this article. This FPD mainly consists of one full‐mode and two half‐mode SIW cavities where each cavity's differential‐mode (DM) and CM are designed reasonably. The filtering DM signals to dual‐ports power division is realized with a simple and compact configuration. Moreover, the CM signals can be naturally rejected without any additional isolation circuits. Ultimately, the BTB FPD with a center frequency of 10.5 GHz is designed, fabricated, and measured to verify the proposed design concept, which shows below −15 dB 6% DM filtering fractional bandwidth (FBW). The CM transmission is suppressed below −22 dB over 28.6% FBW. The proposed design exhibits the advantages of compact size, simple design, low loss, planarity, and multi‐function fusion.